Convergence or disparity? A cross-country analysis of corporate social responsibility reporting for banking industry in Nordic countries and China - Yang, M.; Maresova, P.; Akbar, A.; Bento, P.; Liu, W. (SAGE Open, 2021)
This research investigates the corporate social responsibility (CSR) reporting for banking industry in Nordic countries and China, and compares the convergence and disparity of disclosed CSR information across these two regimes. The study encompasses a sample of eight largest commercial banks by total assets in Nordic countries and China over a 5-year period of 2013–2017. We employ a disclosure index approach to assess the contents of CSR reporting based on eight categories and a total of 60 CSR indicators. The results indicate that Nordic banks have a higher overall disclosure level of CSR information than Chinese banks, and significantly ahead of their counterparts with respect to the international commitment, and a wider coverage of addressing stakeholders’ needs. In contrast, CSR reporting in Chinese banks put greater emphasis on national public policy and philanthropic activities. Nevertheless, all sample countries share a convergence on underlining the importance of complying with applicable laws and regulations. The study findings assert that the convergence and disparity of CSR reporting across countries is relevant to pre-existing socio-political institutions the firms can rely on. This research probes into an unexplored research territory by comparing the CSR reporting between banks from a so-called Nordic business-society model and a Confucian-tradition model. Hence, it entails some important policy prescriptions for the concerned administrators and corporate practitioners in the sample countries.